HAK SERVITUUT DALAM PERSPEKTIF PERTIMBANGAN HAKIM PADA PERKARA PENGABDIAN PEKARANGAN - Vierananda Rosa Setyawati Vierananda Rosa Setyawati; Leli Joko Suryono (Universitas Sains dan Teknologi Komputer, 2025)
This study examines judicial considerations in resolving disputes involving servitude, defined as land servitude rights (hak pengabdian pekarangan), in an access-road conflict decided in Decision Number 102/PDT/2020/PT.YYK. Using a normative juridical method supported by statutory regulations, legal doctrine, court rulings, and supplementary interviews with legal practitioners, the research finds that the judge acknowledged a valid agreement granting the plaintiffs the right to use a portion of the defendant’s land as an access road, subject to compensation. This agreement created a binding land servitude that remained attached to the land regardless of subsequent actions taken by the landowner. The defendant’s act of constructing a wall that blocked the plaintiffs’ only access route constituted an unlawful act that satisfied all elements of Article 1365 of the Indonesian Civil Code, including wrongful conduct, fault, causation, and resulting harm. The novelty of this research lies in its explicit integration of servitude as a real right with the legal doctrine of unlawful acts, thereby offering an analytical bridge rarely explored in Indonesian jurisprudence. The implication of these findings is the necessity for clearer judicial standards and practical guidelines to prevent arbitrary conduct by landowners and to ensure consistent protection of established servitude rights in future disputes.